The Process of Agrarian Reform in the Interwar Lithuania and the Society - Kasperavičius, Algis Povilas (Lietuvos istorijos studijos, 2016)
The article analyses how different social and political groups of interwar Lithuania perceived the on-going agrarian reform, what were their motives behind the decisions to expropriate the estate of landowners and to compensate the loss, how the landowners tried to influence the process of preparation and implementation of the agrarian reform.
Keywords: agrarian reform; interwar Lithuania; Krupavičius; Rimka; landowners